The Effect of Rebranding and Modification of Luxury Brand’s Storytelling on Brand Image - Materlínová, Eva (2024)
Due to the changing trends in society as well as changing generations, luxury brands face a need for continual innovation and adaptation. There is, however, a lack of literature providing theories on luxury rebranding. Therefore, this thesis investigates the impact of rebranding and storytelling on the brand image of luxury fashion brands, with a specific focus on evaluation of rebranding of Dior under the creative director Maria Grazia Chiuri. The study employs a comprehensive approach, combining theoretical frameworks with empirical analysis based on consumer questionnaire. Key findings reveal that while Dior's rebranding efforts have enhanced the brand's personality and emotional connection with younger, socially-conscious consumers, the perception of brand’s luxury and brand strength has declined. The shift from traditional to modern themes such as feminism, diversity, and sustainability has been generally well-received but has also been met with scepticism. Visual storytelling remains a critical factor, with a preference for classical elements that embody traditional luxury. The research underscores the importance of balancing modernity with heritage in luxury branding. Effective storytelling, which integrates both contemporary values and traditional luxury attributes, is essential for maintaining brand prestige and consumer loyalty. The findings offer valuable insights for luxury brands aiming to navigate the complexities rebranding and evolving consumer expectations in a dynamic market. This thesis contributes to the broader understanding of luxury brand management, providing strategic recommendations for leveraging storytelling in rebranding efforts.